The Agricultural Health Study – 2008 Update - Frederick M. Fishel (EDIS)
PI-180, a 2-page fact sheet by Frederick M. Fishel, summarizes the most recent findings from The Agricultural Health Study (AHS) in the following areas: pesticide residues in homes, pesticides and colorectal cancer, and pesticides and diabetes. Includes additional sources of information. Published by the UF Department of Agronomy, May 2009.